The Value of Information in Water Quality Monitoring and Management - Amelie Luhede; Houda Yaqine; Reza Bahmanbijari; Michael Römer; Thorsten Upmann (Center for Economic Studies and ifo Institute (CESifo), 2023)
Environmental managers face substantial uncertainty when deciding on management actions. To reduce this uncertainty prior to decision-making, collecting new data may help arrive at more informed decisions. Whether any resulting improvement in the decision will outweigh the cost of collecting the data, and thus make investing in the acquisition of the information worthwhile, is an intricate question. The concept of the value of information (VoI) is a convenient tool to address this problem. We use the VoI framework to analyse a decision problem in water quality management. Based on real-world monitoring data, we calculate the VoI of monitoring nitrogen, which is used as an indicator of the ecological state of water body. We find that the VoI is significant in our case and we further investigate the dependency of the VoI in a similar setting on the management cost, the assumed value of a good state and on the level of uncertainty regarding the ecological state. In addition, we observe a negative relation between the relative management cost and the prior probability that maximises VoI. These insights may help decide on information acquisition in the presence of substantial uncertainties and sparse data.
Keywords: C11; C61; D81; Q25; Q57; 330; value of information; decision analysis; uncertainty; environmental management; monitoring